2013
DOI: 10.1002/jnr.23185
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic caffeine intake in a mouse model of amyotrophic lateral sclerosis

Abstract: Caffeine is a nonselective adenosine receptor antagonist; chronic consumption has proved protective toward neurodegenerative diseases such as Parkinson's and Alzheimer's diseases. The present study was designed to determine whether caffeine intake affected survival and/or motor performance in a transgenic model of amyotrophic lateral sclerosis (ALS). SOD1(G93A) mice received caffeine through drinking water from 70 days of age until death. Body weight, motor performance and survival were evaluated. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 47 publications
4
46
2
Order By: Relevance
“…A 2A receptors are overexpressed in lymphocytes from ALS patients, resulting in increased levels of intracellular cAMP [51], which highlights a possible role for these receptors in immunosuppressive responses in ALS. Whether the now documented A 2A receptor functional changes in the SOD1(G93A) also parallel with an immunological based response and relate with the previously reported A 2A receptor-mediated delayed onset and reduced progression of motor neuron dysfunction in this ALS model [11], awaits further investigation.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…A 2A receptors are overexpressed in lymphocytes from ALS patients, resulting in increased levels of intracellular cAMP [51], which highlights a possible role for these receptors in immunosuppressive responses in ALS. Whether the now documented A 2A receptor functional changes in the SOD1(G93A) also parallel with an immunological based response and relate with the previously reported A 2A receptor-mediated delayed onset and reduced progression of motor neuron dysfunction in this ALS model [11], awaits further investigation.…”
Section: Discussionmentioning
confidence: 77%
“…A 2A receptors expression was shown to be decreased in the spinal cord of symptomatic SOD1(G93A) animals [11]. Alterations in the transducing system operated by A 2A receptors may also be altered in ALS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our observation indicates that the A 2a R expression is altered at the symptomatic stage, the specific disease stages from which the A 2a R signaling is altered in SOD1G93A mice likely resulted from different regions examined in our study and the previous study (Nascimento et al, 2014). Although chronic administration of caffeine, a non-specific antagonist of all adenosine receptors, significantly shortens overall survival of SOD1G93A mice without obvious effect on the body weight and motor phenotypes (Potenza et al, 2013), this likely resulted from the pan-inhibition of all adenosine receptors, especially the neuroprotective A 1 R.…”
Section: Discussionmentioning
confidence: 99%
“…Although caffeine has neuroprotective effects in animal models of Parkinson's Disease (7), in the only published study in animal models of ALS, caffeine administration was reported to accelerate disease progression and shorten survival in SOD1 mice (29). The results of both epidemiological and experimental studies, therefore, unfortunately suggest that caffeine consumption does not have beneficial effects in the disease process that leads to ALS.…”
Section: Discussionmentioning
confidence: 99%